SILENT VALLEY MOVEMENT IN KERALA: A STUDY ON THE CONTRIBUTIONS OF KERALA SASTRA SAHITYA PARISHAD - Manjusha.K.A (International Journal of Research in Social Sciences, 2016)
The Silent Valley Movement is the tale of a battle against the state to protect a pristine evergreen rainforest in Kerala, South India. The battle for the now famous Silent Valley raged for over ten years and involved thousands of people. When Kerala State Electricity Board announced plans to begin the construction of a 240 MW Hydro Electric Project over the Kunthipuzha river flowing through the Palakkad and Malappuram Districts in 1976, it triggered a wave of protests across the state. Soon, it became India‘s first major environmental movement resulting in far reaching changes. The Protesters were spear-headed by the Kerala Sastra Sahitya Parishad, a voluntary organization to promote scientific temperament, produced hard facts. The movement was undertaken by the environmentalists, poets, artists, academics, thousands of students and the media against the proposed hydroelectric dam across Kunthipuzha in the Western Ghats. The agitation led to the establishment of the 89 sq.km tropical rainforest National Park in 1984 after abandoning the Hydel Project. The present paper is an attempt to trace out the role of different mediums which contributed to the success of the Silent Valley Movement with special reference to the contributions of the Kerala Sastra Sahitya Parishad.